A Comparison of In Vitro Bioavailability of Total Antioxidant Capacity of Selected Organic and Conventional Vegetables: In vitro bioavailability of vegetables - Kanabur, Vaijayanthi Vitthappa; R P, Lalitha Reddy (Food and Applied Bioscience Journal, 2018)
The objective of the study is to know if there is a difference in in vitro bioavailability (also known as in vitro digestibility) of organically and conventionally cultivated vegetables with respect to antioxidant capacity. A method that simulates human digestive system was used to study the in vitro bioavailability of antioxidants present in organically grown and conventionally grown vegetables. Four commonly consumed vegetables namely spinach, tomato, beetroot and carrot were selected for the study. Institute of Marketlogy Organic Certification (I.M.O) certified organic vegetables and conventional vegetables grown in the same soil and agro climatic condition were selected for the study. The vegetables were freeze dried using Lyodryer and stored at 4°C±2 in dark. Four different solvents were used for extraction to identify the best solvent for each vegetable. Total antioxidant capacity was estimated by Ferric Reducing Antioxidant Power (FRAP) method as described by Benzie and Strain (1996). In vitro bioavailability was determined according to a method described by Luten et al (1996). The percent recovery was studied based on the difference between antioxidant capacity of vegetables before and after in vitro digestion. The results indicate that among the vegetables studied, antioxidants in conventional beetroot had the highest recovery after digestion. The recovery of antioxidant capacity after digestion is slightly better for conventional vegetables compared to organic vegetables in case of spinach, beetroot and tomato whereas there was no significant difference in the in vitro bioavailability of organic and conventional carrot.